Rapid onset type-1 diabetes and diabetic ketoacidosis secondary to nivolumab immunotherapy: a review of existing literature. Issue 8 (26th August 2019) - Abdullah, Hafez Mohammad Ammar; Elnair, Radowan; Khan, Uzma Ikhtiar; Omar, Muhammad; Morey-Vargas, Oscar L
Abstract : Nivolumab is a programmed cell death receptor (PD-1) inhibitor that is increasingly used for various malignancies, both as a first line agent and as salvage therapy. Being a PD-1/PD-1 ligand checkpoint inhibitor, it is known to cause autoimmune inflammation of various organs and has been associated with thyroiditis, insulitis, colitis, hepatitis and encephalitis to name a few. There are increasing reports of nivolumab leading to acute onset fulminant type 1 diabetes and diabetic ketoacidosis (DKA). We present a case of a 68-year-old man who developed DKA after 2 doses of nivolumab for metastatic melanoma. He was found to have type 1 diabetes, but no diabetes related antibodies were positive. He recovered from diabetes and continues to use insulin 1 year after his diagnosis. This case and associated review illustrates the importance of educating and monitoring patients who start nivolumab therapy regarding this potentially life threatening complication.